PERANCANGAN APLIKASI PENCARIAN LOKASI BENGKEL RESMI NASMOCO DI KOTA SEMARANG DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Kurniawan, Theofilus; Tanone, Radius (Proceedings of KNASTIK, 2013)
Authorized workshops Nasmoco a formal workshop for Toyota cars are scattered in the city of Semarang and Central Java. There are four authorized workshops in Semarang city. The wide of Semarang city andscattered authorized workshops would make it difficult for owners of Toyota cars and people who want to find workshops in search of the nearest authorized workshop. For ease in searching a place needed an location search application that can display directions directly from the user's location to the destination. The system are built using waterfall method as the design of location search application using Augmented Reality technology.The application development using the Wikitude SDK as the Augmented Reality builder and Global Positioning System (GPS). Location search application using Augmented Reality will facilitate user in finding the location of the nearest service station and obtain other information easily.